The Coupled Magmatic and Hydrothermal Systems of the Restless Aluto Caldera, Ethiopia - Wilks, M.; Rawlinson, N.; Kendall, J.-M.; Nowacki, A.; Biggs, J.; Ayele, A.; Wookey, J. (Frontiers in Earth Science, 2020)
Seismicity can be used to better understand interactions between magma bodies, hydrothermal systems and their host rocks - key factors influencing volcanic unrest. Here, we use earthquake data to image, for the first time, the seismic velocity structure beneath Aluto, a deforming volcano in the Main Ethiopian Rift. Traveltime tomography is used to jointly relocate seismicity and image 3D P- and S-wave velocity structures and the ratio between them (VP/VS). At depths of 4-9 km, the seismicity maps the top of a large low velocity zone with high VP/VS, which we interpret as a more ductile and melt-bearing region. A shallow (< 3km) hydrothermal system exhibits low seismic velocities and very low VP/VS (~1.40), consistent with the presence of gases exsolved from a deeper melt-rich mush body. The Artu Jawa fault and fracture system provides the migration pathway that connects the deeper mush body with the shallow hydrothermal system. Together, these observations demonstrate that the interaction between magmatic and hydrothermal systems, driven by the exchange of fluids, is responsible for the restless behaviour of Aluto.